On the robustness of the fat-tailed distribution of firm growth rates: A global sensitivity analysis - Giovanni Dosi; Marcelo de Carvalho Pereira; Maria Enrica Virgillito (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2016)
Firms grow and decline by relatively lumpy jumps which cannot be accounted by the cumulation of small, "atom-less", independent shocks. Rather "big" episodes of expansion and contraction are relatively frequent. More technically, this is revealed by fat tail distributions of growth rates. This applies across different levels of sectoral disaggregation, across countries, over different historical periods for which there are available data. What determines such property? In Dosi et al. (2015) we implemented a simple multi-firm evolutionary simulation model, built upon the coupling of a replicator dynamic and an idiosyncratic learning process, which turns out to be able to robustly reproduce such a stylized fact. Here, we investigate, by means of a Kriging meta-model, how robust such "ubiquitousness" feature is with regard to a global exploration of the parameters space. The exercise confirms the high level of generality of the results in a statistically robust global sensitivity analysis framework.
Keywords: C15; C63; D21; D83; L25; 330; Firm Growth Rates; Fat Tail Distributions; Kriging Meta-Modeling; Near-Orthogonal Latin Hypercubes; Variance-Based Sensitivity Analysis